INCREASE OF CORTICAL MICRO-CHANNELS (COMICS) AS A NEW FEATURE OF STRUCTURAL DAMAGE IN PAIENTS WITH RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, F.; Berlin, Andreas; Haschka, J.; Renner, Nina; Buder, Thomas; Rech, Jürgen; Engelke, Klaus; Hueber, Axel; Schett, Georg; et al. (2017)
EVALuna2:34454

INTRAARTICULAR MICRO CHANNELS OF MCP JOINTS INCREASE DURING DEVELOPMENT OF RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Rech, Jürgen; Haschka, J.; Buder, Thomas; Neuhuber, Winfried; Schett, Georg; Hueber, Axel; Kleyer, Arnd (2015)
EVALuna2:34457

Rheumatoid arthritis is characterized by early changes of the cortical micro-channel (CoMiC) system in the bare area of the joints - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Haschka, Judith; Renner, Nina; Buder, Thomas; Engelke, Klaus; Hueber, Axel; Rech, Jürgen; et al. (Arthritis and Rheumatology, 2017)
To characterize the specific structural properties of the erosion-prone bare area of the human joint and to search for early microstructural changes in this region during rheumatoid arthritis Methods: An initial cadaveric study was used for exact localization of the bare area of the metacarpal heads, detection of cortical micro-channels (CoMiCs) in this region by high-resolution peripheral computed tomography (HR-pQCT) and, after anatomical dissection, their validation by micro-computed tomography (?CT). In the second part, number and distribution of CoMiCs were analyzed in 105 healthy individuals and 107 RA patients with similar sex and age distribution.HR-pQCT investigation combined with adaptive thresholding allowed detection of CoMiCs in the bare area of cadaveric joints. Their existence in the bare area was additionally validated by ?CT. In healthy individuals, the number of CoMiCs increased with age. RA patients showed significantly (p<0.001) more CoMiCs (112.9±54.7/joint) than healthy individuals (75.2±41.9/joint) with 20-49 years old RA patients exhibiting similar CoMiC numbers as observed in over 65 year old healthy individuals. Importantly, CoMiCs were found in RA patients already very early in their disease course with enrichment in the erosion-prone radial side of the joint.CoMiCs represent a new form of structural change in the joints of patients with RA. While CoMiCs increase with age, RA patients develop such changes much earlier in life and already at the onset of the disease. CoMiCs therefore represent an interesting new opportunity to assess structural changes in RA. This article is protected by copyright. All rights reserved.
EVALuna2:13409